Effects of Sargassum crassifolium Extract Formula as Biostimulant on Growth and Yield of Glycine max L. Merill - Zozy Aneloi Noli; Muhammad Azwar (Jurnal Biologi Tropis, 2021)
The research about the Effect of Sargassum crassifolium Extract Formula as Biostimulant to Increase Growth and Yield of Glycine max L. Merill was conducted from February until June 2020 at the warehouse of Plant Physiology Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, Andalas University, Padang. The research aims to evaluate the effectiveness of liquid and powder extract formula of S. crassifolium as biostimulant on the growth and yield of soybean (Glycine max L. Merill). The research was conducted by an experimental method arrange in a Completely Randomized Design (CRD). The experiment consisted of 3 treatments. Each treatment was laid out with nine replications. The treatments tested were control, liquid extract (0.4%), powder extract (1.6 g/L). The results showed that the application of liquid extract gave a higher tendency towards the improvement of the root system, fresh and dry weight, chlorophyll content, and 100 seeds weight of soybean plant. While the powder extracts shown the best result on the total seed weight. Both of extract formula had the potential to be used to increase growth and yield of soybean.